Anionic Complex with Efficient Expression and Good Safety Profile for mRNA Delivery - Eri Hamada; Tomoaki Kurosaki; Junya Hashizume; Hitomi Harasawa; Hiroo Nakagawa; Tadahiro Nakamura; Yukinobu Kodama; Hitoshi Sasaki (MDPI AG, 2021)
We previously found that a complex comprising plasmid DNA (pDNA), polyethylenimine (PEI), and γ-polyglutamic acid (γ-PGA) had high transgene efficiency without cytotoxicity in vitro and in vivo. However, messenger RNA (mRNA) remains an attractive alternative to pDNA. In this study, we developed a safe and effective delivery system for mRNA to prevent its degradation and efficiently deliver it into target cells. Various cationic and anionic complexes were produced containing PEI, γ-PGA, and an mRNA encoding firefly luciferase. Their physicochemical properties and cytotoxicities were analyzed and the in vitro and in vivo protein expression were determined. The cationic mRNA/PEI complex showed high in vitro protein expression with strong cytotoxicity. The anionic complex was constructed as mRNA/PEI8/γ-PGA12 complex with a theoretical charge ratio of 1:8:12 based on the phosphate groups of the mRNA, nitrogen groups of PEI, and carboxylate groups of γ-PGA. It was stable and showed high in vitro protein expression without cytotoxicity. After intravenous administration of mRNA/PEI8/γ-PGA12 complex to mice, high protein expression was observed in the spleen and liver and slight expression was observed in the lung over 24 h. Thus, the newly constructed mRNA/PEI8/γ-PGA12 complex provides a safe and effective strategy for the delivery of mRNA.